If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -1(2y + -2) = 1 + -3y Reorder the terms: 9 + -1(-2 + 2y) = 1 + -3y 9 + (-2 * -1 + 2y * -1) = 1 + -3y 9 + (2 + -2y) = 1 + -3y Combine like terms: 9 + 2 = 11 11 + -2y = 1 + -3y Solving 11 + -2y = 1 + -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. 11 + -2y + 3y = 1 + -3y + 3y Combine like terms: -2y + 3y = 1y 11 + 1y = 1 + -3y + 3y Combine like terms: -3y + 3y = 0 11 + 1y = 1 + 0 11 + 1y = 1 Add '-11' to each side of the equation. 11 + -11 + 1y = 1 + -11 Combine like terms: 11 + -11 = 0 0 + 1y = 1 + -11 1y = 1 + -11 Combine like terms: 1 + -11 = -10 1y = -10 Divide each side by '1'. y = -10 Simplifying y = -10
| 2x-4(x+3)=x+8 | | 37-5=4x+24 | | 7d-2=4d+13 | | x/4+3=x | | x^2+4x=4x+32 | | 5x+10=2(2x+6) | | 13-8x=143-43x | | -4(4y-8)-y=-2(y-4) | | 3y-12x=15 | | -3(y+3)=2y+21 | | h=5vt+19t^2 | | 4x^2-17x+22=4x+2 | | 3x+8=52-9x | | 8-(4-12t)+2=3t+2(7-3t) | | 3g+4(-8+3g)=1-g | | -5v-31=3(v-5) | | 6+2(3j-2)=4(l+j) | | 8=n*18 | | -8w+6(w-2)=-4 | | 3(x-6)+2x=5(x+2)-28 | | 10-10x=70-24x | | 4(x-20)=24x | | -16+x=10x | | 4(x-20)=24 | | 6p-9=-5p-42 | | 29-3x=-53 | | 30a^6-104a^5=-90a^4 | | 6p-9=5p+42 | | 5x-5y=3 | | a-2(a-16)=7a | | 5x+2=4x-5 | | 7x+18x=75 |